DETERMINANT OF EFFECTIVE TAX RATE: INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLE - Widyaswara, Noerma; Lestari, Yona Octiani (Widya Mandala Surabaya Catholic University, 2025)
Research Purposes. This research examines how capital intensity, leverage, profitability, and sales growth influence effective tax rates, with institutional ownership as a moderating variable. The study measures these factors using Capital Intensity Ratio (CIR), Debt to Equity Ratio (DER), Return on Assets (ROA), Sales Growth (SG), and Institutional Ownership (KI). Research Methods Employing quantitative methodology, the analysis uses multiple linear regression on data from 38 food and beverage companies on the IDX between 2021-2023. These companies were identified through purposive sampling techniques. Research Results and Findings. The findings indicate that capital intensity and return on assets influence the effective tax rate, while debt-to-equity ratio and sales growth show no impact. Furthermore, institutional ownership successfully moderates how capital intensity and return on assets affect the effective tax rate. However, this institutional ownership fails to moderate the relationship between debt to equity ratio, sales growth, and the effective tax rate. Therefore, this research is expected to be useful for company management in order to find out what factors affect the amount of corporate tax payments and in an effort to streamline the company's tax burden according to applicable tax regulations. This research is also expected to be a source of reference and development material for further research in the future related to factors that affect the Effective Tax Rate in Indonesia.